Quality Culture as a Strategic Driver of Teacher Human Resource Development for Fostering Future-Ready Teachers in Islamic Education - Ratna Sari; Herdiana; Zulkhairi (Journal of Educational Management Research, 2026)
This study aims to examine teacher human resource development strategies based on a quality culture in fostering future-ready teachers within Islamic educational institutions. A qualitative case study approach was employed, involving school leaders, teachers, and quality assurance personnel as research participants. Data were collected through in-depth interviews, observations, and document analysis, then analyzed using NVivo through coding, cluster analysis, tree map analysis, and word cloud analysis to identify key themes and relationships. The findings indicate that teacher development is strengthened through continuous professional development, academic supervision, collaborative learning communities, digital literacy enhancement, and the cultivation of a quality-oriented organizational culture. The study also reveals that quality culture promotes continuous improvement, professionalism, collaboration, and innovation while supporting teachers’ adaptability to educational change. Future-ready teachers are characterized not only by digital competence and 21st-century skills but also by strong moral, spiritual, and Islamic values. The integration of teacher human resource development, quality culture, digital literacy, and Islamic values provides a sustainable framework for preparing adaptive, innovative, and ethically grounded teachers capable of responding to future educational challenges.